Proc. 29th Annual Conference of the International Group for Lean Construction (IGLC) 2021
DOI: 10.24928/2021/0208
|View full text |Cite
|
Sign up to set email alerts
|

Lean and BIM Interaction in a High Rise Building

Abstract: Lean Design has been spreading its use in the AEC industry along with the emergence of Building Information Modelling (BIM).Those two methodologies; Lean and BIM are being implemented first independently and then together. as new means to deliver more efficient projects.This paper researches some tools of Lean and BIM that permit a positive interaction by focusing on a case study related to a high rise building for residential use. Those tools are; from Lean Construction, set based design and value stream mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This failure in communication between team members was also noted in the cases studied by Michaud et al (2019aMichaud et al ( , 2019b and Saurin and Sanches (2014). According to Bekdik et al (2016), Chuquín et al (2021aChuquín et al ( , 2021b and Ramalingam (2018), the cause of the defect was linked to the lack of training employees, compromising the quality and performance of the process.…”
Section: Waste Found When Adopting the Value Stream Mapping And Its M...mentioning
confidence: 77%
See 1 more Smart Citation
“…This failure in communication between team members was also noted in the cases studied by Michaud et al (2019aMichaud et al ( , 2019b and Saurin and Sanches (2014). According to Bekdik et al (2016), Chuquín et al (2021aChuquín et al ( , 2021b and Ramalingam (2018), the cause of the defect was linked to the lack of training employees, compromising the quality and performance of the process.…”
Section: Waste Found When Adopting the Value Stream Mapping And Its M...mentioning
confidence: 77%
“…It should be noted that not all the studies analyzed highlighted results or benefits from the VSM application as they did not present either of the two maps (Chuquín et al, 2021a(Chuquín et al, , 2021bEtges, 2018;Michaud et al, 2019aMichaud et al, , 2019b or presented only the construction of the current state map (Aka et al, 2017;Michaud et al, 2019aMichaud et al, , 2019bSaurin and Sanches, 2014;Vilventhan et al, 2019;Xie et al, 2018).…”
Section: Value Stream Mapping Applicationmentioning
confidence: 99%
“…The third most frequent benefit is 'analysis of various design alternatives' (B3). Some characteristics of construction projects, such as unique and multidisciplinary character, complexity and uncertainty, and required financial capital make the analysis of various design options indispensable during the early stages of the projects (Chuquín et al, 2021a;Rempling et al, 2019). Therefore, benefit B3 has a positive effect on ensuring that the design solution generates the value desired by the client and satisfies the requirements that gave rise to the project.…”
Section: Benefits Of Set-based Design Adoptionmentioning
confidence: 99%
“…For example, Chuquín et al (2021b) applied a survey at the end of a design process with SBD, the findings showed that 72% believed that the quality of their work had increased, and rework had decreased. Besides, Chuquín et al (2021a) conducted a survey of the usefulness of SBD among the participants of a case study of a high-rise building. The results showed that 70% of the respondents highlighted the usefulness of SBD and expressed their intention to adopt SBD in future projects.…”
Section: Introductionmentioning
confidence: 99%